(untitled) (Bangladesh Journal of Medical Science, 2017)
Suprapubic catheterization is common urological procedure. Rare complication (less than 10 cases reported) is herniation through trocar insertion site. In this case, 65 years Muslim male with history of urethral stricture presented with a reducible hernia in lower abdomen since 6 months following a trocar assisted suprapubic cystostomy done 1 year back. Lay open of pananterior urethra was done followed by 1 month later, prolene mesh hernioplasty. Bangladesh Journal of Medical Science Vol.16(4) 2017 p.588-590